Children of heaven - LC Purchase Collection (Library of Congress) (United States : Miramax : Buena Vista Home Entertainment, 1998)
Zohre's shoes are gone; her older brother Ali lost them. They are poor, there are no shoes for Zohre until they come up with an idea: they will share one pair of shoes, Ali's. School awaits. Will the plan succeed?
Summary from container.
Not viewed.
Source used: DVD container, Internet movie database.
Mohammad Amir Naji, Amir Farrokh Hashemian, Bahare Seddiqi.
Persian with English language subtitles.
Keywords: Comedy films; Feature films; Family -- Feature